The Development of Proto-Slavic Quantity (from Proto-Slavic to Modern Slavic Languages) - Kapović, Mate (Array, 2005)
This paper discusses the development of the old length (quantity) in Slavic languages. The retainment or the shortening of the old length is thoroughly discussed in all conditions – under stress (acute, circumflex, neoacute) considering the number of the syllables in a word, and in pretonic or posttonic position considering the number of the syllables in a word and the accentual paradigm. The final open syllables are shortened in all Slavic languages. The acute length is preserved only in Czech in mono- and bisyllabic words (vrána). The circumflex is shortened in West Slavic (Czech *dȃ rъ > dar, *zȏ lto > zlato), and it is preserved in Croatian in monosyllables, bisyllables (dȃ r, zlȃ to) and one type of trisyllables (*ȏ lkъ tь > lȃ kat) but shortened elsewhere (*mȏ ldostь > mlȁ dō st, *nȃ golvǫ > nȁ glā vu). The neo-acute length is preserved in all languages in all positions (Čakavian pũ t, Czech pout'). The pretonic length is preserved in front of less than two moras (Croatian tráva, kobása, gúmno, kúkolj, grà dskī ) and shortened in front of two or more moras (Croatian mà lina, jè zik). In mobile paradigm, the short forms are generalized in West Slavic (Czech hlava). In number of forms, the length is secondarily reintroduced (Croatian, Czech zábava, pítati, súsjed/soused). The posttonic length is preserved in Croatian in trisyllabic words (pȁ mē t, pȁ mē ti) and shortened in longer ones (pȁ metan). In West Slavic, it is shortened in a. p. c (Czech holub) and preserved inconsistently in a. p. a (Czech měsíc, pamět'). In Štokavian/Čakavian, dialects differ in preservation of the posttonic length in a. p. a which is shortened under the acute in a. p. b and a. p. c (glȅ dati : dial. glȅ dā ti). A number of secondary developments and levellings are also discussed.